Active infrared thermography applied to the study of a painting on paper representing the Chigi's family tree. (March 2015) - Pucci, M.; Cicero, C.; Orazi, N.; Mercuri, F.; Zammit, U.; Paoloni, S.; Marinelli, M.
Abstract : In this work, active infrared thermography was applied to study a seventeenth-century painting on paper, namely the Chigi's family tree, housed at Palazzo Chigi in Ariccia (Rome). Thermography was performed before and after restoration to obtain information used in planning the restoration and also to assess its effectiveness. Infrared thermography provided important information on the artifact structure, areas of damage, structural defects, and the state of adhesion between different layers of the composite artifact before and after the treatment.